Microstructure of minerals and yerba mate extract co-crystallized with sucrose - Deladino, Lorena (2010)
Co-crystallization with sucrose is an interesting alternative for handling and preservation of different active compounds used in the food industry. Sucrose products containing different active compounds (calcium lactate, magnesium sulphate and yerba mate extract) were obtained by co-crystallization. The microstructure of these products and raw materials was analyzed by Differential Scanning Calorimetry (DSC), X-rays Diffraction (XRD) and Scanning Electron Microscopy (SEM). The co-crystallized products showed the basic crystalline structure of the treated sucrose without active compound. Mineral distribution in the co-crystallized products was uniform as seen by Energy Dispersive X-rays (EDX). DSC and X-rays analysis showed that the salts were partially dehydrated during the process, yielding products with a crystalline sucrose matrix and, both, anhydrous and hydrated forms of the salts. This characterization helped understanding macroscopic behaviour of the products.